2017
DOI: 10.1016/j.mimet.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis detection towards chlorophenols using video processing analysis

Abstract: To our knowledge, this communication is the first report of chemotaxis towards chlorophenols by any bacteria. We used a recently published method based on the agarose in-plug assay combined with video processing analysis and we also present a new index of bacterial mean speed for these assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Chlorophenols were able to attract P. aeruginosa and Achromobacter marplatensis in swarm plate assays. The authors used a new method of video processing to calculate chemotaxis index and concluded that this behavior must be helpful in degradation of chlorophenols [108]. Chemotaxis of E. coli to phenol has been reported where the organism was found to exhibit both attractant and repellent mechanisms to phenol [109].…”
Section: ) Nitrophenols Nitrobenzoates and Their Derivativesmentioning
confidence: 99%
“…Chlorophenols were able to attract P. aeruginosa and Achromobacter marplatensis in swarm plate assays. The authors used a new method of video processing to calculate chemotaxis index and concluded that this behavior must be helpful in degradation of chlorophenols [108]. Chemotaxis of E. coli to phenol has been reported where the organism was found to exhibit both attractant and repellent mechanisms to phenol [109].…”
Section: ) Nitrophenols Nitrobenzoates and Their Derivativesmentioning
confidence: 99%